2009
DOI: 10.1590/s1413-78522009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Gel de plaquetas: arcabouço 3D para cultura celular

Abstract: Introduction: Tissue repair has been the ultimate goal of surgery. Cell culture requires a mechanical scaffold that supports cell growth and nutrient diffusion. Using platelet-rich plasma (PRP) as a 3D scaffold presents various advantages: it is a biological material, easily absorbed after transplantation, rich in growth factors, in particular, PDGF-ββ and TGF-β that stimulate extracellular matrix synthesis in cartilage culture. Objective: To develop a PRP 3D scaffold. Material and Methods: Two forms were idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
2
Order By: Relevance
“…These data indicated that α7β1 was sensitive to PRP and alignment and that α7 and β1D were not mediating MyoG and MyHC increases. Instead, these increases might be influenced by inherent ECM proteins in PRP like fibrinogen and fibronectin [37][38][39][40], or by the effect of PRP on ECM synthesis [4,41].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that α7β1 was sensitive to PRP and alignment and that α7 and β1D were not mediating MyoG and MyHC increases. Instead, these increases might be influenced by inherent ECM proteins in PRP like fibrinogen and fibronectin [37][38][39][40], or by the effect of PRP on ECM synthesis [4,41].…”
Section: Discussionmentioning
confidence: 99%
“…Vários destes métodos biológicos encontram-se associados à Engenharia de Tecidos [62][63][64] . Como in vivo, os tecidos projetados in vitro devem fornecer transporte de nutrientes, estabilidade mecânica, coordenação de processos multicelulares e um microambiente celular que preserve a estabilidade fenotípica das células [65] . Dentre os hidrogéis aplicáveis à engenharia de tecido cartilaginoso, o AH é um GAGs presente na matriz extracelular do tecido cartilaginoso, que fornece um microambiente capaz de manter a homeostase e preservar o estado diferenciado dos tecidos.…”
Section: Aplicação De Hidrogéis a Base De áCido Hialurônico E Quitosaunclassified
“…Sophisticated 3D cultures using scaffolds—or scaffolding—can be generated using several natural polymers (collagen, elastin, fibrin, chitosan, alginate, fibrinogen, and platelet-rich plasma), synthetic materials, which include PLLA (poly (L-lactic acid)), PGA (poly (glycolic acid)), elastomeric polyurethanes, decellularized tissues and organs, and others [ 18 , 19 , 20 , 21 , 22 , 23 ]. The main challenge in scaffold designing is to mimic the presence of the ECM, a network of fibrous proteins, primarily collagen, embedded in a highly hydrated gel of glycosaminoglycans, proteoglycans, and glycoproteins [ 11 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%